Malaysian lemongrass (Cymbopogon citratus) (DC.) Stapf as natural antimicrobials for enhancing food safety : identification, characterisation and application : a thesis presented in partial fulfilment of the requirements for the degree of Doctoral of Philosophy in Food Microbiology at Massey University, Palmerston North, New Zealand - Mohd Daud, Ili Syuhada (Massey University, 2025)
This study investigates the antimicrobial potential of lemongrass (Cymbopogon citratus) nanoemulsion against Bacillus cereus, a resilient foodborne pathogen known for its spore-forming ability, toxin production, and biofilm-forming capacity. The research adopts a multi-phase approach encompassing extraction, formulation, comparative efficacy, and mechanistic understanding to explore the viability of lemongrass-based nanoemulsions as natural antimicrobial agents for food safety. In Chapter 3, supercritical fluid extraction (SFE) was employed to extract essential oils from two Malaysian lemongrass varieties, Gajah and Peha Ayam under varying pressures (85 to 300 bar). Peha Ayam extracted at 85 bar yielded the highest citral content (90.06%) and showed the strongest antibacterial activity. Emulsified extracts demonstrated enhanced antimicrobial efficacy, especially in soy milk, while higher carbohydrate content in rice milk was associated with reduced performance. These findings highlight the importance of extract quality, formulation, and food matrix compatibility in determining antimicrobial effectiveness. Chapter 4 presents a comparative assessment of lemongrass and citral nanoemulsions against the conventional antimicrobial nisin across three B. cereus isolates (ATCC 14579, P4, and M2). While nisin exhibited strong planktonic inhibition, lemongrass nanoemulsion consistently outperformed both nisin and citral in biofilm disruption and prevention assays, suggesting its superior performance in managing biofilm-related contamination in food systems. Chapter 5 further characterizes the nanoemulsions’ physicochemical properties, noting strong initial stability and bactericidal activity. However, droplet coalescence over time reduced long-term efficacy. Notably, whole lemongrass nanoemulsions retained bioactivity longer than citral nanoemulsions, indicating the possible synergistic role of minor constituents. Chapter 6 focuses on the antibacterial mechanism. A series of mechanistic assays revealed that lemongrass nanoemulsion disrupts bacterial membranes, leading to ATP depletion, membrane depolarization, and cell lysis. These effects were confirmed via flow cytometry, fluorescence microscopy, and transmission electron microscopy (TEM), highlighting its concentration-dependent action and isolate-specific responses. Collectively, this thesis establishes lemongrass nanoemulsion as a promising clean-label antimicrobial with potential applications in food preservation, offering new insights into its formulation, mechanism, and commercial viability.
Keywords: Natural antimicrobials; Nanoemulsions; Bacillus cereus; Biofilm; Food preservation; Anti-infective agents; Lemongrass; Analysis; Essences and essential oils; 30 Agricultural, veterinary and food sciences::3006 Food sciences::300607 Food technology